IMPLEMENTATION OF SCHOOL BASED MANAGEMENT TO IMPROVE THE QUALITY OF ISLAMIC EDUCATION AT MTS NEGERI 1 IN PALU CITY - Zaid, Zaid (Risâlah, Jurnal Pendidikan dan Studi Islam, 2021)
The study aims to describe the implementation of school based management to improve the quality of Islamic Education. The study was qualitative approach in MTs Negeri 1 Palu. The study results showed that (1) Madrasah independence can be seen in the availability of educators and education personnel and the availability of adequate facilities and infrastructure. (2) Madrasah partnerships/cooperation are good; this can be seen from the madrasah's internal relations that have been well established through working meetings, briefings, and MGMPs. Meanwhile, with external parties, it can be proven that the madrasa has established a relationship with the institution by being proven by the MoU. (3) The implementation of the program is managed by each component of the madrasa, by preparing written implementation instructions such as K13 document, organizational structure, division of tasks for teachers and education staff, academic regulations, and madrasa rules. (4) Program evaluation is more focused on academic programs than on learning and teacher performance effectiveness and efficiency, implementing Madrasah Self Evaluation and Madrasah accreditation. and the Inspectorate General (IRJEN) of the Ministry of Religion.